Rational design of high-performance continuous-flow microreactors based on gold nanoclusters and graphene for catalysis - Liu, Yanbiao; Liu, Xiang; Yang, Shengnan; Li, Fang; Shen, Chensi; Huang, Manhong; Li, Junjing; Nasaruddin, Ricca Rahman; Xie, Jianping (American Chemical Society, 2018)
In this work, we rationally designed a high-performance microreactor system for continuous-flow catalysis. The membrane consists of ultrasmall gold nanoclusters (AuNCs) and two-dimensional graphene. The Au cores of the NCs act as catalysts, while their ligands have two functions: (1) protecting the Au cores to avoid agglomeration and (2) providing a well-defined surfactant assembly to disperse graphene in aqueous solution. Hydrogenation of 4-nitrophenol (4-NP) was employed as model reaction to evaluate catalytic activity. The catalytic membrane microreactor demonstrated excellent catalytic activity and stability, where complete 4-NP conversion was readily achieved via a single pass through the membrane. This desirable performance was maintained over 12 h of continuous operation, although a certain amount of organic buildup on the membrane was observed. The catalytic membrane microreactor outperforms conventional batch reactors due to its improved mass transport. 4-NP-spiked real water samples were also completely converted. This study provides new insights for the rational design of membrane reactors for industrial applications.